The effect of age on neural processing of pleasant soft touch stimuli - May, April C.; Stewart, Jennifer L.; Paulus, Martin P.; Tapert, Susan F. (Frontiers in Behavioral Neuroscience, 2014)
Tactile interactions with our environment stimulate afferent fibers within the skin, which deliver information about sensations of pain, texture, itch and other feelings to the brain as a comprehensive sense of self. These tactile interactions can stimulate brain regions involved in interoception and reward processing. This study examined subjective, behavioral, and neural processing as a function of age during stimulation of A-beta (Aβ) and C tactile (CT) afferents using a soft brush stroke task. 16 adolescents (ages 15-17), 22 young adults (ages 20-28), and 20 mature adults (ages 29-55) underwent a simple continuous performance task while periodically anticipating and experiencing a soft touch to the palm or forearm, during functional magnetic resonance imaging (fMRI). fMRI results showed that adolescents displayed greater bilateral posterior insula activation than young and mature adults across all conditions and stimulus types. Adolescents also demonstrated greater bilateral posterior insula activation than young and mature adults specifically in response to the soft touch condition. Adolescents also exhibited greater activation than mature adults in bilateral inferior frontal gyrus and striatum during the soft touch condition. However, mature adults showed greater striatum activation than adolescents and young adults during anticipation. In the left anterior cingulate cortex, mature adults exhibited greater activation than adolescents and young adults when anticipating the upcoming touch. These results support the hypothesis that adolescents show an exaggerated neural response to pleasant stimulation of afferents, which may have profound effects on how they approach or avoid social and risky situations. In particular, heightened interoceptive reactivity to pleasant stimuli might cause adolescents to seek experiences that are associated with pleasant stimulation.